Decoding the Digital World: How Digital Literacy Skills Support Language Acquisition - Hutagalung, Genta Ulina (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
Abstract Digital literacy is an essential component of language learning. This study aims to explore the way digital literacy skills can be used in supporting students' language acquisition by reviewing existing research. This paper focuses on how students' digital competences such as information and data literacy, communication and collaboration, digital content creation, safety and problem solving could help them in their language acquisition process. Articles from several sources are reviewed to analyse this problem. As a result of this study, this paper intends to explore how digital literacy skill could be used to support language acquisition, particularly discussing about the digital competences. The findings of this paper show that all of the elements of digital literacy can support students’ language acquisition in many ways. Therefore, it is concluded that digital literacy in language learning is very important in the current education setting.